Expert evaluation of the traditional Malay Medicine Kitab Tib Melayu database - Basar, Muhammad Alif; Mohd Shafri, Mohd Affendi; Mohamed, Farahidah; Abu Seman, Muhamad Sadry (Malaysian Journal of Library and Information Science, 2025)
The Traditional Malay Medicine Kitab Tib Melayu Database (TMM-KTMDB) was developed to digitally preserve, organise, and systematise Traditional Malay Medicine (TMM) knowledge from historical manuscripts. For a digital resource to be credible and usable across research, education, and policy contexts, its usability, reliability, and data accuracy must be evaluated. Expert feedback testing was conducted using two instruments: a task assignment and a feedback questionnaire. Quantitative responses were analysed using section scores and an overall score to assess usability across system components. Qualitative feedback was examined through thematic interpretation, focusing on polarity and themes including usability, system functionality, content quality, and information accuracy. Task-based testing demonstrated excellent usability across the search engine, guest accessibility, system functionality, and repository application, with overall scores ranging from 86% to 100%. Thematic analysis identified content and information quality (92.6%) and system functionality (50%) as major strengths. Weaknesses centred on search functionality (64.3%) and glossary clarity (21.4%). Opportunities were noted for content expansion (71.4%) and support features. The findings affirm TMM-KTMDB as a functional and content-rich digital knowledge system while highlighting areas for improvement in information retrieval, glossary development, and interface design. From a library and information science (LIS) perspective, structured expert evaluation supports validation of organisation, accessibility, and trustworthiness. The evaluation indicates that TMM-KTMDB aligns with expectations for a reliable digital resource for Traditional Malay Medicine. Continued refinement will further strengthen usability, accuracy, and relevance for research, education, clinical practice, and policy within the medical and health sciences domain.